Density Functional Theory Study of Hydrogenated $MAl_{12}$ $(M = Al,Li,Na,K)$ Clusters (Journal of Atomic and Molecular Sciences, 2021)
The structure and electronic properties of bare and hydrogenated metal $(M=Al,Li,Na,K)$ embedded $Al_{12}$ cage clusters have been investigated systematically by density functional theory calculations. It has been found that the most stable $Al_{12}H_{12}$ and $MAl_{12}H_{12}$ clusters possess icosahedral symmetry. The stability analysis shows that hydrogenation of clusters enhances the stability of aluminum clusters, and $LiAl_{12}H_{12}$ is the most stable of all clusters considered. Mulliken population analysis indicates that significant charge transfer occurs between alkali atoms and $Al$ atoms. The higher electron density on the $H$ atoms in relation to the deformation electron density shows that electron is partially transferred from $Al$ atoms to hydrogen upon adsorption.